Morphological Analysis of Derivational Affixes Used in Eka Kurniawan’s Novel Beauty is a Wound Translated by Annie Tucker - Siti Fatimah; Zumrotul Muniroh (Candradimuka: Journal of Education, 2023)
This research aims to analyze the derivational affixes which contained in Beauty is A Wound novel. The data of research containing derivational affixes in Beauty is A Wound novel, and use that novel as the sources of data in this research as real process of data information. The writer uses descriptive qualitative method in analyzing the data. The data is based on Katamba’s theory of derivational affixes. As the result of the research, the writer found 744 derivational affixes, which consists 114 derivational prefixes and 630 derivational suffixes. The most frequent data on the novel is 326 derivational suffix –ly (43.82%), then 78 prefix un- (10.49%), 77 suffix –er (10.35%), then 45 suffix –al (6.05%), next is 42 suffix –ity (5.65%), followed by 37 suffix –ness (4.98%), the next is 33 suffix –ful (4.44%), after that 28 suffix –ment (3.77%), followed by 26 suffix –less (3.50%), next is 13 prefix in- (1.75%), then 12 prefix re- (1.62%), followed by 9 prefix dis- (1.21%), and 7 suffix –ship (0.95%), then 7 suffix –ic (0.95%), and 2 suffix –hood (0,08%), and the lowest is 2 prefix en- (0,08%).